Energy-efficient OpenMP Programming - Karlsson, Axel; Valter, Henrik (My University, 2022)
OpenMP is the de facto API for parallel programming in HPC applications. These programs are often computed in data centers, where energy consumption is a major issue. Whereas previous work has focused almost entirely on performance, we here analyse aspects of OpenMP from an energy consumption perspective. This analysis is accomplished by executing novel microbenchmarks and common benchmark suites on data center nodes and measuring the energy consumption. Three main aspects are analysed: directive-generated loop tiling and unrolling, parallel for loops and explicit tasking, and the policy of handling blocked threads. For loop tiling and unrolling, we find that tiling can yield significant energy savings for some, mostly unoptimised programs, while directive-generated unrolling provides very minor improvement in the best case and degenerates performance majorly in the worst case. For the second aspect, we find that parallel for loops yield better results than explicit tasking loops in cases where both can be used. This becomes more prominent with more fine-grained workloads. For the third, we find that significant energy savings can be made by not descheduling waiting threads, but instead having them spin, at the cost of a higher power consumption. We also analyse how the choice of compiler affects the above questions by compiling programs with each of ICC, Clang and GCC, and find that while neither is strictly better than the others, they can produce very different results for the same compiled programs. As a final step, we combine the findings of all results and suggest novel compiler directives as well as general recommendations on how to reduce energy consumption in OpenMP programs.
Keywords: OpenMP; energy efficiency; compiler optimisations; loop tiling; loop unrolling